Stock Returns and Inflation: Evidence from Emerging Markets in Asia - Isnandari, Melati Laksmindra; Chalid, Dony Abdul (UI Scholars Hub, 2017)
This study examines the capability of stock from various industries to act as an inflation-hedge instrument, specifically in eight emerging-market Asian countries. By using monthly data for the period from 2001 to 2014, this study focuses on the relation between stock returns and inflation. The results of this study indicate that stocks from some non-cyclical industries have the capability to act as inflation-hedge instruments. Stocks that have the capability to inflation-hedge are come from industries with the natural characteristic of being a defensive industry.